Carbosilane Dendrimers Loaded with siRNA Targeting Nrf2 as a Tool to Overcome Cisplatin Chemoresistance in Bladder Cancer Cells - Leanne Ambrosio; Monica Argenziano; Marie Angèle Cucci; Margherita Grattarola; Inge A.M. de Graaf; Chiara Dianzani; Giuseppina Barrera; Javier Sánchez Nieves; Rafael Gomez; Roberta Cavalli; Stefania Pizzimenti (MDPI AG, 2020)
The transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2) is considered as the master regulator of antioxidant and cytoprotective gene expressions. Moreover, it plays a pivotal role in cancer progression. Nrf2 mediates the adaptive response which contributes to the resistance to chemotherapeutic pro-oxidant drugs, such as cisplatin (CDDP), in various tumors, including bladder cancers. For this reason, Nrf2 could be a promising target to overcome chemoresistance. There are several known Nrf2 pharmacological inhibitors; however, most of them are not specific. The use of a specific small interfering RNA (siRNA) targeting the Nrf2 gene (siNrf2) loaded into nanovehicles is an attractive alternative, since it can increase specificity. This study aimed to evaluate the biological activity of siNrf2 loaded on guanidine-terminated carbosilane dendrimers (GCDs) in overcoming CDDP resistance in bladder cancer cells with a high level of Nrf2. Parameters such as viability, proliferation, apoptosis, migration, and oxidative stress level were taken into account. Results demonstrated that siNrf2-GCD treatment sensitized CDDP-resistant cells to CDDP treatment. Moreover, data obtained by treating the non-cancerous human kidney HK-2 cell line strongly suggest a good safety profile of the carbosilane dendrimers loaded with siNrf2. In conclusion, we suggest that siNrf2-GCD is a promising drug delivery system for gene therapy to be used in vivo; and it may represent an important tool in the therapy of CDDP-resistant cancer.